Effects of different activating fluxes on the surface tension of molten metal in gas tungsten arc welding. (April 2018) - Li, Chunkai; Shi, Yu; Gu, YuFen; Fan, Ding; Zhu, Ming
Abstract: Surface tension is an important factor in arc welding and affects weld microstructure and flow mode in the weld pool. A novel surface tension measurement method based on the principle of weld pool oscillation is proposed to sense the surface tension of the weld pool without and with TiO2, NaCl, and CaF2 activating fluxes during tungsten inert gas welding process. Experimental results reveal that the TiO2 activating flux can convert the surface tension gradient from negative to positive but exerts minimal effect on arc behavior. The surface tension gradient is mainly controlled by the oxygen content in the weld pool, which determines the Marangoni convection and penetration depth. High oxygen content decreases the surface tension gradient and weakens the Marangoni convection in the weld pool. The NaCl and CaF2 activating fluxes can reduce the absolute value of average surface tension but exert negligible effects on the sign of surface tension gradient. The varied surface tension and increased penetration depth with NaCl and CaF2 activating fluxes are caused by arc constriction and increased arc temperature, respectively.